Ð§Ñ‚Ð¾ Ð¼Ñ‹ ÐµÑ‰Ðµ Ð½Ðµ Ð·Ð½Ð°ÐµÐ¼ Ð¾ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ñ… ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð°Ñ…? - Gorskaya, A. Yu.; Goltsev, A. N.; Lutsenko, E. D. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
The authors performed a comparative analysis of modification of immunogenic properties of syngeneic heat-treated and cryopreserved erythrocytes on their ability to induce autoimmune hemolytic anemia (AIHA) in an organism of experimental animals. There was established the fact of appearance of immunogenic properties in syngeneic erythrocytes after all types of the mentioned pre-treatment. In a comparative aspect it has been shown that maximum manifested immune response to syngeneic erythrocytes as the production of autoantibodies (AABs) is observed after their heat treatment at 49.5Â°C. The erythrocytes, cryopreserved with 30% glycerol had less manifested immunogenic properties than those heated, but similar to the erythrocytes cryopreserved with PEO-1500, they induced the development of autoimmune reaction approximately in 50% of mice-recipients. Obtained results testify to a modification of antigenic spectrum of erythrocytes under the effect of cryopreservation factors. The modification of erythrocyte membrane structures is likely the result of realization of the freeze-thawing effect, since the influence of cryoprotectants on this process as â€œit isâ€ is minimal.